2021
DOI: 10.3390/ijms22105064
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Overexpression of Histone H3K4 Methyltransferase CsSDG36 from Tea Plant Decreases Hyperosmotic Stress Tolerance in Arabidopsis thaliana

Abstract: Histone methylation plays an important regulatory role in the drought response of many plants, but its regulatory mechanism in the drought response of the tea plant remains poorly understood. Here, drought stress was shown to induce lower relative water content and significantly downregulate the methylations of histone H3K4 in the tea plant. Based on our previous analysis of the SET Domain Group (SDG) gene family, the full-length coding sequence (CDS) of CsSDG36 was cloned from the tea cultivar ‘Fuding Dabaich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The analysis of cis-elements in the promoter regions allowed the prediction of potential mechanisms of StSET gene regulation. Our results showed that a diverse set of cis-elements were present in most StSET genes (Table 4), indicating that the StSET genes are involved in several diverse biological processes, including drought [39], anaerobic induction, auxin responsiveness, defense, stress responsiveness, wound, and low-temperature responsiveness (Fig. 4).…”
Section: Discussionmentioning
confidence: 83%
“…The analysis of cis-elements in the promoter regions allowed the prediction of potential mechanisms of StSET gene regulation. Our results showed that a diverse set of cis-elements were present in most StSET genes (Table 4), indicating that the StSET genes are involved in several diverse biological processes, including drought [39], anaerobic induction, auxin responsiveness, defense, stress responsiveness, wound, and low-temperature responsiveness (Fig. 4).…”
Section: Discussionmentioning
confidence: 83%
“…The analysis of cis-elements in the promoter regions allowed the prediction of potential mechanisms of StSET gene regulation. Our results showed that a diverse set of cis-elements were present in most StSET genes (Table 3), indicating that the StSET genes are involved in several diverse biological processes, including drought [45], anaerobic induction, auxin responsiveness, defense, stress responsiveness, wound, and low-temperature responsiveness (Fig. 4).…”
Section: Set Domain-containing Gene Family In Potatomentioning
confidence: 83%
“…The phenotype of stomatal density reduction and cell wall thickening induced by singlet oxygen has important implications for agricultural industry. Declines in stomatal density would enhance plant's tolerance to drought ( 36 , 37 , 38 , 39 , 40 ), salinity/osmotic stress ( 38 , 39 , 40 , 41 , 42 ), and heat stress ( 40 , 43 , 44 ) by reducing water transpiration. There are interests in developing crop varieties that require less water yet still maintain the grain yield.…”
Section: Discussionmentioning
confidence: 99%